Corporate balance sheet adjustment: Stylized facts, causes and consequences - Eric Ruscher; Guntram B. Wolff (Bruegel, 2012)
We analyse corporate balance sheet adjustment episodes in Germany and Japan, as well as a sample of 30 countries, using national account data. Corporate balance sheet adjustment tends to be long lasting and associated with a strong impact on current accounts, wages and investment. Adjustment episodes lead to significant changes in corporate balance sheet ratios with a buildup of liquidity and a reduction of leverage. The adjustment is generally achieved by reducing investment and increasing savings on the back of a falling wage share. A panel econometric exercise shows that balance sheet adjustment periods are triggered by macroeconomic downturns as well as balance sheet stress due to high debt, low liquidity and negative equity price shocks.
Keywords: 330; Kapitalstruktur; Fremdkapital; Konjunktur; Deutschland; Japan